2018
DOI: 10.1038/s41419-018-1062-3
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Na/H exchanger stimulates glioma tumor immunogenicity and enhances combinatorial TMZ and anti-PD-1 therapy

Abstract: The weak immunogenicity of gliomas presents a barrier for effective immunotherapy. Na/H exchanger isoform 1 (NHE1) maintains alkaline intracellular pH (pHi) of glioma cells and acidic microenvironment. In addition, NHE1 is expressed in tumor-associated microglia and tumor-associated macrophages (TAMs) and involved in protumoral communications between glioma and TAMs. Therefore, we hypothesize that NHE1 plays a role in developing tumor resistance and immunosuppressive tumor microenvironment. In this study, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 67 publications
(74 reference statements)
2
53
0
Order By: Relevance
“…These proteins are often overexpressed and co-opt this protective mechanism to inhibit immune activation. Immune checkpoint blockade therapies have shown remarkable clinical success for some cancers, including metastatic melanoma 140,146,147 . In 2016, anti-PD1 mAb Nivolumab was FDA-approved for recurrent/metastatic HNSCC patients with progressive disease or failure of platinum-based therapy.…”
Section: The Genetic Landscape In Hnscc and Its Clinical Implicationsmentioning
confidence: 99%
“…These proteins are often overexpressed and co-opt this protective mechanism to inhibit immune activation. Immune checkpoint blockade therapies have shown remarkable clinical success for some cancers, including metastatic melanoma 140,146,147 . In 2016, anti-PD1 mAb Nivolumab was FDA-approved for recurrent/metastatic HNSCC patients with progressive disease or failure of platinum-based therapy.…”
Section: The Genetic Landscape In Hnscc and Its Clinical Implicationsmentioning
confidence: 99%
“…Furthermore, blocking Na + /H + exchange decreases tumor growth and stimulates MG immunogenicity, besides increasing the effect of temozolomide (TMZ) [34,84]. Most surprisingly, these authors also reported that TMZ increases NHE1 protein levels in human glioblastoma cells, a feature that not only could increase TMZ resistance, but raises serious doubts about a possible deleterious effect of TMZ in the treatment of MG. On the other hand, the combination of TMZ and cariporide in a mouse glioma xenograft model significantly prolonged the survival of the mice in the same report.…”
Section: Towards a New Perspective And Clinical Approach To Malignmentioning
confidence: 99%
“…Some studies had demonstrated that a distant organ as a site of tumor metastasis is not a passive receiver of circulating tumor cells but is actively selected and well prepared before the seeding of circulating tumor cells (Peinado et al 2017 ). Chronic deregulation of cytokine expression and activity can result in tumor initiation, growth, and metastasis (Peinado et al 2017 ; Itatani et al 2016 ; Guan et al 2018 ; Hou et al 2017 ). Abnormal expression and secretion of cytokines not only remodels the tumor microenvironment, but also suppresses the capability of immune cells to kill tumor cells (Xiao et al 2018 ; Caraci et al 2018 ; Tan et al 2018 ; Siveen et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%